The long-term impact of religion on social capital: lessons from post-war Czechoslovakia - Stepan Mikula; Tommaso Reggiani; Fabio Sabatini (Masaryk University, Faculty of Economics and Administration, 2023)
We exploit a historical experiment that occurred in Czechoslovakia after World War Two to study the drivers of social capital accumulation in an extremely unfavorable environment. Between 1945 and 1948, the Sudetenland became the scene of ethnic cleansing, with the expulsion of nearly three million German speakers and the simultaneous influx of nearly two million resettlers. Focusing on the areas where at least 90 % of the population was forced to leave, we show that the municipalities hosting a church built before 1945 developed significantly higher social capital under the communist rule, which persisted after the dissolution of Czechoslovakia and the current days.
Keywords: D74; L31; N24; N44; N94; O15; Z1; 330; Institutions; migration; conflict; social capital; religion; transition countries